2018
DOI: 10.1111/joie.12179
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline Price Dispersion and Consumer Search: Evidence from a Natural Experiment

Abstract: The vast majority of empirical studies examining the link between consumer search and price dispersion focus on how changes in consumer search impact price dispersion. This article does the reverseit examines how a shock to price dispersion impacts consumer search. A direct measure of search is used and an exogenous shock to price dispersion is found in a refinery fire that caused decades-old retail gasoline price cycles, and the nonlinear high-frequency price dispersion pattern generated by them, to stop. Ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…GasBuddy.com is a crowdsharing website where interested drivers can report recently observed gasoline prices for use by other drivers who also use the site. 7 GasBuddy price data has been widely used in academic research (e.g., Lewis and Marvel [2011]; Atkinson et al [2014]; Noel [2018a]) and is shown to give a good representation of the distribution of gasoline prices at a point in time (Atkinson [2008]). 8 Summary statistics on prices from the complete dataset are given in Table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GasBuddy.com is a crowdsharing website where interested drivers can report recently observed gasoline prices for use by other drivers who also use the site. 7 GasBuddy price data has been widely used in academic research (e.g., Lewis and Marvel [2011]; Atkinson et al [2014]; Noel [2018a]) and is shown to give a good representation of the distribution of gasoline prices at a point in time (Atkinson [2008]). 8 Summary statistics on prices from the complete dataset are given in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…4 Pennerstorfer et al [2020] show that gasoline price dispersion depends on the fraction of commuters in the area who are presumably more informed. , Byrne and de Roos [2015] and Noel [2018a] all exploit retail gasoline price cycles (Noel [2007]) to examine how shocks to price dispersion, for reasons other than search, affect consumer search itself.…”
Section: Literaturementioning
confidence: 99%
“…Dorn et al [35] promoted the stance that the structure, strategy and policy operated by an organisation are some of the predetermined factors that keep shaping and reshaping the nature of the organisation's behaviour towards competition. Further on the debate of organisation and motivators of competition, other scholars argued for interpersonal relationship and corporate identity as major movers of firm's competition, especially in the aviation industry [36][37][38][39]. Ceptureanu et al [40] concluded in their work that competitive performance has significant implication on the overall benefits and outcome of the organisation's performance/ sustainability.…”
Section: Empirical Literaturementioning
confidence: 99%
“…This phenomenon was not studied by the classical theory, but in recent decades, by the efforts of many researchers, this gap has largely been overcome, but only with the assumption of a hypothesis of a single price. The question of how the variation in retail prices in wholesale jumps has attracted the attention of researchers recently, in particular Noel [12], based on retail gas prices (known as Edgeworth price cycles), has established a two-way link between price dispersion and consumer search. The search activity not only affects the variance, as it was well documented, but the price variance also affects the search.…”
Section: Related Workmentioning
confidence: 99%